Development of Automated Fire Control System: An Integrated Solution for Gas, Fire, and Smoke Detection - Syed Saad Ali; Shujaat Ali; Sajjad Ali; Asad A. Zaidi; Ahsan Zafar; Saqib Munawwar; Muhammad Shafique (Pakistan Journal of Engineering Technology & Science)
The major shortcomings of gas, fire, and smoke detection must be addressed to prevent accidents. Gas leaks, fires, and smoke-related incidents pose a significant threat to the country. The main objective of this prototype is to develop a system that detects, manages, and issues immediate alerts for gas leaks, fires, and smoke, thus enabling swift responses to mitigate potential harm. This prototype highlights the importance of household safety by developing an integrated system to detect, control, and manage gas, fire, and smoke incidents. Conventional systems often lack the necessary automation and speed required for effective emergency responses. This project addresses the critical need to automate the detection and control of such dangers. Gas leaks and fires can lead to rapid and severe damage, highlighting the importance of rapid detection and response. This project utilizes an advanced methodology that integrates gas sensors, flame sensors, smoke sensors, and automated control mechanisms. The system automatically secures a leak of gas utilized in cylinders or pipes. For fires, it deploys water sprinklers to suppress flames, whereas fans automatically clear smoke. The implementation of an Arduino-based system automatically controls the system. Flame, gas, and smoke sensors were integrated with the Arduino to control and manage the system. Sensors and Arduino mathematical calculations were also monitored. This prototype is designed to monitor detection over a 100 cm span. Inspired by the latest technologies, this prototype addresses the critical need for household safety by automating the detection, control, and management of gas, fire, and smoke incidents.